Molecular analysis of Hemagglutinin Gen of Highly Pathogenic Avian Influenza of H5N1 Subtype Isolated from Waterfowls - Susanti, R; Soejoedono, Retno D; K Mahardika, I Gusti Ngurah; T Wibawan, I Wayan; Suhartono, Maggy T (Indonesian Animal Sciences Society, 2008)
Avian influenza viruses (AIV) subtype H5N1 isolated from waterfowls in West Java pose the known characteristic of highly pathogenic strains, with polybasic amino acid sequence of cleavage site QRERRRKKR and QRESRRKKR. This research aimed to analyze the important domains of hemagglutinin (HA) gene of those isolates. Fragment of HA gene was amplified using RT-PCR method with specifically-designed primer pairs and sequenced using dideoxy termination method with ABI automatic sequencer (Applied Biosystems). Multiple alignment of nucleotide and deduced amino acid sequences were analyzed using ClustalW of MEGA-3.1 program. Some of biological domains of HA, i.e. antigenic sites, receptor binding pocket, and glycosylation sites of the isolates were polymorphic. The viruses also pose conserved glutamine (Q) and glisin (G) residues at the known receptor binding site, at the position 222 and 224 respectively. This findings clearly show that all AIV subtype H5N1 isolaed from waterfowl preservesthe Î±-2,3NeuAcGal avian receptor specificity. Key Words: Antigenic Sites, Glycosylation Sites, Receptor Binding Pocket, AIV H5N1, Waterfowls